Tributação e economia digital - SIlva, Alan Cintra Soledade da (2024)
This monograph investigates the adaptations of tax systems to the digital economy. Using an interdisciplinary analytical approach based on literature reviews, the study highlights the challenges of tracking and taxing digitally generated value in a borderless market. It emphasizes the need for innovative and flexible tax reforms, adapted to rapid technological dynamics and the virtual business environment, ensuring equitable distribution of the tax burden, and strengthening global oversight. The Digital Services Tax in France exemplifies the adaptation of tax systems to include digital entities, with OECD efforts reinforcing the need for international cooperation